Developing Practical, Useful Educational Technology Applications for Course Designers, Teachers and Language Learners: An Interview with Laurence Anthony - Stephen Jeaco (Cranmore Publishing, 2021)
Professor Laurence Anthony is probably best known for his corpus tools - including the freeware concordancer called AntConc. He is also known for his contributions to fields of English for Specific Purposes (ESP), Natural Language Processing (NLP) and Educational Technology. In this interview, Laurence Anthony talks about the early beginnings of his interests in science, programming and language learning; some of the background to AntConc; his views on needs analysis and other aspects of English for Specific Purposes; and his perspectives on machine feedback and machine evaluation.